Pengaruh Tingkat Inflasi, Suku Bunga, Harga Emas, Nilai Tukar, dan Indeks Harga Saham Gabungan terhadap Kinerja Reksa Dana Saham Syariah Periode 2017-2021 - Nugroho Widi Sasongko (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the influence of variable inflation, interest rates, gold prices, exchange rates, and composite stock price indices on the performance of Islamic stock mutual funds. The data used are 8 sharia stock mutual fund data registered with the Financial Services Authority (OJK) in the 2017-2021 period. Data analysis techniques are carried out by classical assumption testing, hypothesis testing using multiple linear regression analysis. The results showed that inflation, interest rates, gold prices, rupiah exchange rates against the US dollar (USD) and JCI simultaneously had a significant effect on the performance of Islamic stock mutual funds. Partial inflation with a regression value of 0.0403, interest rate with a regression value of 0.0361, gold price with a regression of 0.0428, and exchange rate with a regression of 0.0002 has a significant effect on mutual fund performance. As for the JCI with a regression value of 0.05218, there is no significant influence on the performance of Islamic stock mutual funds.